Cultivating the heart : feeling and emotion in twelfth- and thirteenth-century religious texts - Lazikani, Ayoush Sarmada, 1987- (Religion & culture in the Middle Ages., 2015)
Cultivating the Heart reveals the languages of feeling in a range of religious texts from the High Middle Ages.